A review on wireless home network technologies. - Vaxevanakis, K. (Mobile computing and communications review.)
Connecting residences to broadband access networks offers an unprecedented opportunity to extend the networking customer base beyond the satiated corporate environment. Yet despite this promising prospect, the market is evolving very tenuously: on one hand, there are numerous industrial consortia and standardization bodies that continue their work on independent and often non-interoperable specifications for residential networks; on the other hand, while there are multiple home PCs and multimedia network-enabled appliances, the majority of the houses can not support sophisticated interconnection, while most consumers are unwilling or cannot afford a large scale home rewiring. Among many competing technologies, wireless networks can resolve the rewiring issue capturing a major percentage of the Home Network market. In this paper, we review the available technologies in the home network area, and provide a comparison of the wireless broadband in-home technologies